Women's movements in twentieth-century Taiwan - Chang, Doris T., 1969- (University of Illinois Press, 2009)
This book is the first in English to consider women's movements and feminist discourses in twentieth-century Taiwan. Doris T. Chang examines the way in which Taiwanese women in the twentieth century selectively appropriated Western feminist theories to meet their needs in a modernizing Confucian culture. She illustrates the rise and fall of women's movements against the historical backdrop of the island's contested national identities, first vis-à-vis imperial Japan (1895-1945) and later with postwar China (1945-2000). --From publisher's description.